SYSTEMATIC REVIEW OF CONSUMER RESISTANCE TO AI DRIVEN PERSONALIZATION - Muhammad Ali (Penelitian dan Pengembangan Ilmu, 2025)
The integration of artificial intelligence (AI) into marketing personalization strategies has created a paradox between service efficiency and consumer resistance. This study aims to synthesize the dominant psychological factors that trigger consumer resistance to AI-based personalization through a conceptual approach.narrative reviewBy analyzing literature from Scopus, Web of Science, and PsycINFO databases (2015–2025), this study identified three main clusters of resistance: cognitive antecedents (intrusiveness and privacy), affective antecedents (algorithmic anxiety and fear of manipulation), and threats to individual autonomy and agency. The synthesis of results shows that perceived vulnerability (79%) far outweighs perceived convenience benefits (62%), which is exacerbated by the “black box” nature of AI. The study concludes that mitigating resistance requires a transition from simply algorithmic accuracy to transparent and humanistic AI design. The theoretical contribution lies in the integrationCommunication Privacy Management Theory, Psychological Reactance Theory, and Social Cognitive Theory serves as a unified framework for understanding digital resistance. Practically, this study offers marketers guidance on building trust through empowering user control.